An example of one-step MLE-process in volatility estimation problem - Gasparyan, S. B.; Yu. A. Kutoyants (Հայաստանի ԳԱԱ)
We consider the problem of construction of asymptotically efficient estimator for Pearson diffusion with unknown parameter in the volitility coefficient.
Keywords: Mathematics; Science